The Influence of Nutrition on Intestinal Permeability and the Microbiome in Health and Disease - Orsolya Inczefi; Péter Bacsur; Tamás Resál; Csilla Keresztes; Tamás Molnár (Frontiers in Nutrition, 2022)
The leakage of the intestinal barrier and the disruption of the gut microbiome are increasingly recognized as key factors in different pathophysiological conditions, such as irritable bowel syndrome (IBS), inflammatory bowel disease (IBD), chronic liver diseases, obesity, diabetes mellitus, types of cancer, and neuropsychiatric disorders. In this study, the mechanisms leading to dysbiosis and “leaky gut” are reviewed, and a short summary of the current knowledge regarding different diseases is provided. The simplest way to restore intestinal permeability and the microbiota could be ideal nutrition. Further therapeutic options are also available, such as the administration of probiotics or postbiotics or fecal microbiota transplantation.